Quality improvement in neonatal care through enhanced patient safety and clinical risk management: a before-and-after study about neonatal sepsis - Ferorelli, Davide; Goffredo, Vito Maria; Graziano, Elena; Mastrapasqua, Maurizio; Telegrafo, Michele; Vinci, Annachiara; Visci, Paolo; Benevento, Marcello; Zotti, Fiorenza; Foglianese, Alessandra; Panza, Raffaella; Solarino, Biagio; et al. (Frontiers in Medicine, 2024)
Introduction Neonatal sepsis, classified into early-onset and late-onset based on symptom timing, poses significant risks of morbidity and mortality, especially in low birth weight infants. Effective clinical risk management protocols are crucial in reducing these risks. Methods This before-and-after study evaluated the impact of a newly implemented clinical risk management protocol in the Neonatology and Neonatal Intensive Care Unit (NICU) at Policlinico Hospital-University of Bari. The study included 399 neonates over three years, comparing pre- and post-protocol outcomes. Data collection focused on maternal and neonatal demographics, infection rates, and hospital stay lengths. Statistical analysis included t-tests, Wilcoxon-Mann–Whitney tests, and logistic regression models. Results The study found no significant differences in neonatal pathologies or demographics between pre- and post-protocol groups. However, post-protocol implementation showed a notable reduction in umbilical venous catheter (UVC) infections (p = 0.018) and improved hospital stay lengths. Blood and urine cultures did not show significant changes in microbial patterns post-protocol. Discussion The findings underscore the effectiveness of structured clinical risk management protocols in enhancing neonatal outcomes, particularly in reducing specific infection risks. Despite the study’s limitations, including its observational nature and sample size, the results advocate for broader adoption and further research on these protocols in diverse healthcare settings. The positive outcomes highlight the importance of continuous clinical risk management efforts in high-risk neonatal environments.